The Women’s Participation in Digital Economy in ASEAN - Nengsi, Fitriani (Journal of Islamic World and Politics, 2019)
Digital economy over the past decade has become popular trend in the world, including in ASEAN. ASEAN, which is the sixth largest economy in the world, enjoys the revenue of the digital economy that reaches 150 billion USD per year. Digital economy’s great potential has been widely utilized by society, especially women in ASEAN to improve their standard of living. This paper aims to explain the development of women's participation in digital economy in ASEAN and accompanied by obstacle. The research method is qualitative method with literature study used secondary data. The results of this study indicate large increased in participation of women in digital economy living in urban areas and small increased of women living in rural areas in ASEAN. Understanding of this research may contribute to the improvement and enhancement of women's participation in digital economy, especially for women living in rural areas in ASEAN.